(untitled) (Archive of Conferences, 2021)
The article examines the linguistic verbalization of the concept of "beauty" in Uzbek classical poetry, in particular, in the works of the 15th century poets. The implementation of this cognitive process through folk sayings, phraseological units and individual expressions is analyzed. The lexical-semantic, cognitive-pragmatic foundations of connections between lexical units are analyzed.